Tangible–Intangible Factors Interaction on Hostility Escalation and Rivalry Endurance: The Case of India–Pakistan Rivalry. (August 2015) - Sitaraman, Srini
A major contribution of the enduring rivalry literature is that the same pair of states—commonly referred to as dyads—are the cause for the majority of violent territorial changes and low-intensity conflicts. Enduring rivalries account for almost half of the militarized disputes during the past 200 years. Expanding literature on enduring rivalries informs us that militarized disputes and crises are influenced by past outcomes, internal dynamics of conflict behaviour and the prospects of future disputes. This article focuses on the India–Pakistan enduring rivalry, which has persisted for 68 years, and this rivalry is marked by four wars, and numerous instances of asymmetric warfare. The India–Pakistan rivalry has proved to be the most enduring, and it simply does not show any sign of abatement, and this conflict has become nested within the Pakistan–Afghanistan and India–China regional rivalry and territorial dispute. In addition, the India–Pakistan enduring rivalry has also become deeply enmeshed in the American-led Global War on Terrorism (GWOT). This article reviews the vast literature on enduring rivalry with particular focus on India–Pakistan to examine what factors have led to the persistence and exacerbation of this rivalry and why it is displaying no inclination towards termination.